1999
DOI: 10.1007/bf01388171
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of optically active 2-amino-4-oxobutyric acid and N,O-protected derivatives

Abstract: Strategies for the synthesis of optically active aspartaldehyde derivatives are reviewed. Most of them are using the chiral pool: allylglycine or naturally occurring homoserine, aspartic acid or methionine and side chain modifications. This will be developed in the first part. Some other original routes are also displayed in the second part. Different aspects of each strategy are discussed: the nature and number of steps, the problem of protecting groups, the price and availability of starting materials. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…In solution, ASA is an unstable compound that polymerizes (16,50,64,79). We tested the hypothesis that ASA might cyclize to produce a compound analogous to L-azetidine-2-carboxylic acid, a toxic proline analogue.…”
Section: Discussionmentioning
confidence: 99%
“…In solution, ASA is an unstable compound that polymerizes (16,50,64,79). We tested the hypothesis that ASA might cyclize to produce a compound analogous to L-azetidine-2-carboxylic acid, a toxic proline analogue.…”
Section: Discussionmentioning
confidence: 99%
“…Research in our laboratories has recently focused on the synthesis of unusual amino acids (Reginato et al, 1997(Reginato et al, , 1998(Reginato et al, , 1999Meffre et al, 1999Meffre et al, , 2001Meffre, 1999;Dave et al, 2003) and in the course of our studies we reported the first synthesis of ethynyloxazolidine 1 (Fig. 1).…”
mentioning
confidence: 62%
“…2 ASA manipulation has also proved to be important in the synthesis of pharmaceuticals, aroma and flavour chemicals, pesticides and herbicides, dyes and pigments. 5 ASA is difficult to synthesize and characterize since, like many amino aldehydes, it has a marked tendency to polymerize and is only stable in aqueous strong acid. [3][4][5] There are three methods for synthesizing (S)-ASA that are commonly used for biochemical studies.…”
Section: Introductionmentioning
confidence: 99%
“…5 ASA is difficult to synthesize and characterize since, like many amino aldehydes, it has a marked tendency to polymerize and is only stable in aqueous strong acid. [3][4][5] There are three methods for synthesizing (S)-ASA that are commonly used for biochemical studies. 3,6,7 The later methods 3,7 are derived from the original method of Black and Wright 6 which requires the ozonolysis of (S)-allylglycine.…”
Section: Introductionmentioning
confidence: 99%